The improvisation of musical dialogue : - Benson, Bruce Ellis (Cambridge University Press, 2003)
The book brings together a wide range of musical examples from classical music, jazz, early music and other genres. Incorporating analytic and continental philosophy, musicology and performance-practice issues, it is a provocative study for philosophers of art and musicologists. It also appeals to general readers; especially those who perform.